Dimerisation of the Yeast K+ Translocation Protein Trk1 Depends on the K+ Concentration - Kulik, Natalia; Kale, Deepika; Spurna, Karin; Shamayeva, Katsiaryna; Hauser, Fabian; Milic, Sandra; Janout, Hannah; Zayats, Vasilina; Jacak, Jaroslaw; Ludwig, Jost (International journal of molecular sciences, 2022)
In baker's yeast (Saccharomyces cerevisiae), Trk1, a member of the superfamily of K-transporters (SKT), is the main K+ uptake system under conditions when its concentration in the environment is low. Structurally, Trk1 is made up of four domains, each similar and homologous to a K-channel α subunit. Because most K-channels are proteins containing four channel-building α subunits, Trk1 could be functional as a monomer. However, related SKT proteins TrkH and KtrB were crystallised as dimers, and for Trk1, a tetrameric arrangement has been proposed based on molecular modelling. Here, based on Bimolecular Fluorescence Complementation experiments and single-molecule fluorescence microscopy combined with molecular modelling; we provide evidence that Trk1 can exist in the yeast plasma membrane as a monomer as well as a dimer. The association of monomers to dimers is regulated by the K+ concentration.
Keywords: Saccharomyces cerevisiae; proteiny přenášející kationty; transportní proteiny; biologický transport; draslík; Biological Transport; Carrier Proteins; translokace genetická; Fungal Proteins; buněčná membrána; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; fungální proteiny; Potassium; Cation Transport Proteins; Cell Membrane; Translocation, Genetic